MHD Slip Flow of Upper-Convected Casson and Maxwell Nanofluid over a Porous Stretched Sheet: Impacts of Heat and Mass Transfer - V.Seethamahalakshmi,; Rekapalli, Leelavathi; T.S.Rao,; P.Naga Santoshi,; G.V.R.Reddy,; Oke A.S, (CFD Letters, 2023)
The significance of this study lies in the exploration of the effects of thermal radiation and convective boundaries on magnetohydrodynamic slip flow over a nonlinear porous stretching surface. Applications range from aiding heat transfer enhancement in electronic devices and renewable energy systems to facilitating understanding in magnetic confinement fusion research and liquid metal cooling systems. The primary goal of this study is to determine how thermal radiation and convective boundaries affect the upper Maxwell Casson convected nanofluid boundary layer flow's magnetohydrodynamic slip flow over a nonlinear porous stretching surface. From the controlling PDEs, nonlinear ODEs are obtained by applying compatible similarity transformations. The quantities related to scientific and engineering concepts, such as skin friction, Sherwood number, and heat exchange, as well as other effects on momentum, temperature, and material concentration, are shown and explained in diagrams. The numerical solution of the current study and the shooting technique is achieved using the Runge-Kutta Fehelberg method. According to the results, increasing the magnetic field causes a decrease in velocity profiles. Additionally, as the velocity slip parameter increases, the local Nusselt number and the local Sherwood number fall.